Evolutionary transition-transversion bias by the example of the cytb gene of palearctic Muridae (Rodentia) and Vespertilionidae (Chiroptera) - Mezhzherin, S.V.; Morozov-Leonov, S.Y.; Zhalay, O.I.; Kokodiy, S.V.; Tereshchenko, V.O.; Rostovskaya, О.V.; Tsyba, A.O. (Доповіді НАН України, 2023)
A comparative analysis of the features of the transition-transversion bias of the nucleotide sequence of the cytb gene
in microbats (Vespertilionidae, Chiroptera) and mice (Muridae, Rodentia) shows both general regularities and certain
family-level features. A common feature of the two families is the fact of the sharp predominance of transitions
over transversions at the early stages of the evolutionary process, followed by the equalization of the ts/tv-displacement
at the species and genus levels of divergences, as well as the fact that the increase in the frequency of transitions
in phyletic lineages is gradual, and the transition is intermittent. At the same time, the levels of spontaneous mutations
and evolutionary drift, as well as the rate of ts/tv drift compensation, are specific to families. These circumstances
do not make it possible to obtain comparable estimates of divergence in different phyla and cause insurmountable
difficulties in creating a universal formula for molecular clocks. Порівняльний аналіз особливостей транзитивно-трансверсивного зсуву нуклеотидної послідовності гена
cуtb гладконосих (Vespertilionidae, Chiroptera) і мишачих (Muridae, Rodentia) показує як загальні закономірності, так і певні особливості родинного рівня. Загальними для двох родин є факт різкого переважання
переходів над трансверсіями на ранніх етапах еволюційного процесу з наступним вирівнюванням ts/tv-зміщення на видовому та родовому рівнях дивергенцій, а також та обставина, що зростання частоти транзицій у філетичних рядах носить поступовий характер, а транзицій — стрибкоподібний. При цьому рівень спонтанного мутування та еволюційного зсуву, а також швидкість компенсації ts/tv зсуву є специфічними
для родин. Ці обставини не дають можливості отримати порівнянні оцінки дивергенції в різних філумах і
спричиняють непереборні труднощі для створення універсальної формули молекулярних годин.